Nutrient Cycling through Litter Production of Shortrotation Trees and its Effect on Herbage and Oil Yield of Aromatic Plants under Agroforestry System - Mohsin, Faiz; Singh, J. P. (Indian Forester, 2007)
Higher herbage and oil yield was recorded in pure fields of Mentha crops than their crops grown under Poplar and Eucalyptus stands. The first harvest of each crop of Mentha spp., yielded higher fresh herbage as well as oil in comparison to second harvest, both in pure as well as intercropped with Poplar and Eucalyptus stands. Maximum herb and oil yield was produced by M. arvensis and minimum by M. piperita, both in pure as well as intercropped stands. The trees intercropped with M. arvensis produced higher quantity of litter and minimum was in M. piperita. The quantity of litter production was higher in poplar than Eucalyptus. The concentration of nutrients (NPK) in the litter decreased with increasing age of stands. It was higher in Poplar than Eucalyptus. The total addition of nutrients was also recorded higher in Poplar than Eucalyptus.